FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TANI WORTEL: SEBUAH ANALISIS REGRESI LINIER BERGANDA - Lilis Suriyani; Djoko Soejono (JSEP (Journal of Social and Agricultural Economics), 2022)
Carrots are widely cultivated by the people of Kandangtepus Village and become their main livelihood. This study aims to determine the characteristics, income, and factors that affect the income of carrot farming in Kandangtepus Village. The research method uses descriptive and analytical methods. The sampling method used quota sampling and snowball sampling. Methods of data collection using interviews and document studies. The data analysis method used descriptive analysis, income analysis, and multiple linear regression. The results showed the characteristics of the business; namely, most of them used privately owned land, capital from personal savings and loans from collectors, inputs that were easily obtained, labor achieved, implementation of carrot cultivation in accordance with the recommendations, yields sold to collectors, and carrot farming. Get support from farmer groups. Carrot farming with two cropping patterns is equally profitable, but carrot farming using an intercropping pattern will produce less than optimal carrot production. Factors that have a significant influence on the income of carrot farming are selling price, production amount, seed cost, fertilizer cost, and labor cost.